Mobile platform for exploring the potential of volunteered geographic information for asset register - Solemon B.; Ariffin I.; Azmi N.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Balloons; Global positioning system; Mobile computing; Mobile phones; Mobile radio systems; Radio frequency identification (RFID); Crowdsourcing; Geographic information; Mobile applications; Mobile communication technology; Mobile platform; Utility companies; volunteered geograhic information; Volunteered geographic information; Mobile telecommunication systems